( x-2) ^4=( x-2
Giải giúp mik bài này ik
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{x+8}{3}+\frac{x+7}{2}=-\frac{x}{5}\)
\(\Leftrightarrow\frac{10\cdot\left(x+8\right)}{30}+\frac{15\left(x+7\right)}{30}=\frac{-6x}{30}\)
\(\rightarrow10x+80+15x+105=-6x\)
\(\Leftrightarrow31x+185=0\)
\(\Leftrightarrow x=-\frac{185}{31}\)
b,\(b,\frac{x-8}{3}+\frac{x-7}{4}=4+\frac{1-x}{5}\)
\(\Leftrightarrow\frac{20\left(x-8\right)}{60}+\frac{15\left(x-7\right)}{60}=\frac{240}{60}+\frac{12\left(1-x\right)}{60}\)
\(\rightarrow20x-160+15x-105=240+12-12x\)
\(\Leftrightarrow47x-517=0\)\(\Leftrightarrow x=11\)
Đặt : \(\dfrac{x}{5}=\dfrac{y}{3}=k\)
`=>x=5k,y=3k`
Ta có : \(x^2-y^2=4=>\left(5k\right)^2-\left(3k\right)^2=4\\ =>25k^2-9k^2=4\\ =>16k^2=4\\ =>k^2=\dfrac{1}{4}\\ =>k=\pm\dfrac{1}{2}\)
\(=>\left[{}\begin{matrix}\left\{{}\begin{matrix}x=\dfrac{5}{2}\\y=\dfrac{3}{2}\end{matrix}\right.\\\left\{{}\begin{matrix}x=-\dfrac{5}{2}\\y=-\dfrac{3}{2}\end{matrix}\right.\end{matrix}\right.\)
`a)\sqrt{16x+48}+\sqrt{x+3}=15` `ĐK: x >= -3`
`<=>4\sqrt{x+3}+\sqrt{x+3}=15`
`<=>5\sqrt{x+3}=15`
`<=>\sqrt{x+3}=3`
`<=>x+3=9<=>x=6` (t/m).
`b)\sqrt{x^2-4}-3\sqrt{x-2}=0` `ĐK: x >= 2`
`<=>\sqrt{x-2}(\sqrt{x+2}-3)=0`
`<=>[(\sqrt{x-2}=0),(\sqrt{x+2}=3):}`
`<=>[(x-2=0),(x+2=9):}<=>[(x=2(t//m)),(x=7(t//m)):}`
ĐKXĐ: \(x\ne\pm2\)
\(\dfrac{x+1}{x-2}=\dfrac{2}{x^2-4}\)
\(\Rightarrow\dfrac{\left(x+1\right)\left(x+2\right)}{x^2-4}=\dfrac{2}{x^2-4}\)
\(\Rightarrow\left(x+1\right)\left(x+2\right)=2\)
\(\Leftrightarrow x^2+3x+2=2\)
\(\Leftrightarrow x^2+3x=0\)
\(\Leftrightarrow x\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-3\end{matrix}\right.\) (thỏa mãn)
đkxđ: \(x ≠2; x ≠-2\)
\(\dfrac{x+1}{x-2}=\dfrac{2}{x^2-4}\)
\(⇔\dfrac{(x+1)(x+2)}{x^2-4}=\dfrac{2}{x^2-4}\)
\(⇔(x+1)(x+2)=2\)
\(⇔x^2+3x=0\)
\(⇔x(x+3)=0\)
\(⇔\left[\begin{array}{} x=0\\ x+3=0 \end{array} \right.\)
\(⇔\left[\begin{array}{} x=0\\ x=-3 \end{array} \right.\)
\(6,\\ a,\\ 1,A=x^2+3x+7=\left(x+\dfrac{3}{2}\right)^2+\dfrac{19}{4}\ge\dfrac{19}{4}\)
Dấu \("="\Leftrightarrow x=-\dfrac{3}{2}\)
\(2,B=\left(x-2\right)\left(x-5\right)\left(x^2-7x+10\right)=\left(x-2\right)^2\left(x-5\right)^2\ge0\)
Dấu \("="\Leftrightarrow\left[{}\begin{matrix}x=2\\x=5\end{matrix}\right.\)
\(b,\\ 1,A=11-10x-x^2=-\left(x+5\right)^2+36\le36\)
Dấu \("="\Leftrightarrow x=-5\)
\(\sqrt{x^2-2x+4}+\sqrt{x^2+5}=9-2x\left(đk:x\le\dfrac{9}{2}\right)\)
\(\Leftrightarrow x^2-2x+4+x^2+5+2\sqrt{\left(x^2-2x+4\right)\left(x^2+5\right)}=81-36x+4x^2\)
\(\Leftrightarrow2\sqrt{\left(x^2-2x+4\right)\left(x^2+5\right)}=2x^2-34x+72\)
\(\Leftrightarrow4\left(x^2-2x+4\right)\left(x^2+5\right)=4x^4+1156x^2+5184-136x^3+288x^2-4896x\)
\(\Leftrightarrow4x^4-8x^3+36x^2-40x+80=4x^4-136x^3+1444x^2-4896x+5184\)
\(\Leftrightarrow128x^3-1408x^2+4856x-5104=0\)
\(\Leftrightarrow128x^2\left(x-2\right)-1152x\left(x-2\right)+2552\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(128x^2-1152x+2552\right)=0\)
\(\Leftrightarrow x=2\left(tm\right)\)(do \(128x^2-1152x+2552>0\))